2018
DOI: 10.1101/460220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcium imaging in freely-moving mice during electrical stimulation of deep brain structures

Abstract: After decades of study in humans and animal models, there remains a lack of consensus regarding how the action of electrical stimulation on neuronal and non-neuronal elementse.g. neuropil, cell bodies, glial cells, etc.leads to the therapeutic effects of neuromodulation therapies. To further our understanding of neuromodulation therapies, there is a critical need for novel methodological approaches using state-of-the-art neuroscience tools to study neuromodulation therapy in preclinical models of disease. In t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…To characterize the network effect of DBS, Paulk et al mapped the cortical responses evoked by single-pulse electrical stimulation delivered via intracranial electrodes in epilepsy patients and confirmed that DBS evoked broad network responses that were stimulation location and pulse parameter dependent 26 . Finally, using cellular fluorescent calcium imaging techniques, a couple of recent studies in animal models demonstrated that DBS altered the relationship of intracellular calcium dynamics and behavior, supporting a network effect of DBS [27][28][29] .…”
mentioning
confidence: 90%
“…To characterize the network effect of DBS, Paulk et al mapped the cortical responses evoked by single-pulse electrical stimulation delivered via intracranial electrodes in epilepsy patients and confirmed that DBS evoked broad network responses that were stimulation location and pulse parameter dependent 26 . Finally, using cellular fluorescent calcium imaging techniques, a couple of recent studies in animal models demonstrated that DBS altered the relationship of intracellular calcium dynamics and behavior, supporting a network effect of DBS [27][28][29] .…”
mentioning
confidence: 90%
“…However, the connectivity and cellular composition influences the population responses during DBS (83) and these factors differ considerably between deep brain structures and the cortex (84)(85)(86). Therefore, it will be important to experimentally determine how waveform asymmetry modulates activation of neural subtypes in the cortex and deeper brain structures (87) and how their respective activity changes over timescales relevant to symptom relief (88).…”
Section: Implications For Neural Technologymentioning
confidence: 99%
“…Lastly, Dr. Ludwig highlighted the need for understanding the mechanisms by which electrical stimulation interacts with neuronal and non-neuronal elements-e.g., neuropil, cell bodies, glial cells, etc., because there remains a lack of consensus regarding how electrical stimulation leads to the therapeutic effects during neuromodulation therapies such as deep brain stimulation. He gave an example of a novel experimental paradigm combining subthalamic nucleus electrical stimulation with single-photon calcium imaging of the dorsal striatum via a head-mounted miniature microscope in healthy and 6-hydroxydopamine-lesioned Parkinsonian mice during minimally constrained behavior capable of measuring stimulation-evoked changes in neural activity (25).…”
Section: Prof Warren Grill Duke University Usamentioning
confidence: 99%